This place is crowded : Japan - Cobb, Vicki; Lavallee, Barbara (New York : Walker, 1992)
Describes transportation, education, home life, holidays, and other aspects of life in the heavily populated island nation of Japan.
Keywords: Japan -- Social life and customs -- 1945-iterature.; Japan -- Social life and customs